COVID-19 outcomes in patients with rheumatoid arthritis with biologic or targeted synthetic DMARDs - James Cheng-Chung Wei; Jih-Jin Tsai; Li-Teh Liu; Chun-Hong Chen; Liang-Jen Chen; Shiow-Ing Wang (RMD Open)
Objectives We aimed to investigate the role of rheumatoid arthritis (RA) with biologic or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARD) exposure in COVID-19 outcomes.Methods Our study retrieved data from the US Collaborative Network in TriNetX between 1 January 2018 and 31 December 2022. We investigated b/tsDMARD use for RA: interleukin 6 inhibitor (IL-6i), Janus-associated kinase inhibitors (JAKi) or tumour necrosis factor-alpha inhibitors (TNFi, reference group). The outcomes of COVID-19 were the incidence of infection and adverse outcomes (hospitalisation, critical care services, mechanical ventilation and mortality). The HR and 95% CI of the outcomes were calculated between propensity score-matched (PSM) patients with different b/tsDMARDs.Results After PSM, 2676 JAKi vs 2676 TNFi users and 967 IL-6i vs 967 TNFi users were identified. As for COVID-19 incidence, JAKi users did not reach statistical significance (HR: 1.058, 95% CI: 0.895 to 1.250) than TNFi users. RA with JAKi users had a significant risk for hospitalisation (HR: 1.194, 95% CI: 1.003 to 1.423), mortality (HR: 1.440, 95% CI: 1.049 to 1.976) and composite adverse outcomes (HR: 1.242, 95% CI: 1.051 to 1.468) compared with TNFi users. Mortality risk tended to be significantly higher in the JAKi group without COVID-19 vaccination (HR: 1.511, 95% CI: 1.077 to 2.121). IL-6i users compared with TNFi users did not have the above findings.Conclusions RA with JAKi users had a significant risk for hospitalisation, mortality or composite adverse outcomes, especially higher mortality among those without COVID-19 vaccination. COVID-19 vaccination should be encouraged in these target cohorts. When using JAKi for patients with RA, clinicians should be vigilant about these adverse outcomes to prevent their occurrence or detect them early for early intervention.